Chemometric Analysis of Iron, Manganese, and Zink Contents for Ground Water Quality Assessment around the Candi Industrial Estate of Semarang City (Universitas Negeri Semarang, 2022)
Water is the most important natural resource for humans and its function cannot be replaced with other compounds. Most people use ground water and surface water to meet their daily needs. Several factory production activities in the Candi Industrial Estate of Semarang have a role in protecting the environment, especially related to pollution of the aquatic environment in the surrounding area. Some of the potential liquid waste that make pollute into the environment such as Iron (Fe), Manganese (Mn), and Zinc (Zn). The purpose of this study was to measure the levels of heavy metals Fe, Mn, and Zn in groundwater around the Semarang Candi Industrial Estate by using chemometric analysis using Principal Component Analysis (PCA) and Cluster Analysis (CA) methods. Data on the levels of Fe, Mn, and Zn have been analyzed by PCA and CA methods using SPSS 22 application software. The results in this study indicate that mostly of water sample from Candi Industrial Estate reliable with clean water quality standard, just there is one area that have the content of heavy metal levels of Fe of 1 mg/L, which means that it is above the standard threshold for clean water quality set by the Regulation of the Indonesian Minister of Health Number 32 of 2017. The results obtained in PCA analysis formed 2 main components, namely PC1 and PC2 consist of three contaminants, while in the CA method 4 large clusters were formed in the research area of location.